An Unpublished Manuscript of the Correspondence of the Doge of Venice Francesco Donato to the Podestà of the City of Buje (16th Century) - Pekić, Radmilo B.; Mitić, Marija N. (Collection of Papers of the Faculty of Philosophy in Priština, 2024)
The 16th-century records produced by the office of the Venetian Doge comprise a rich collection of official documents. They were written according to the rules of ars dictaminis and represent important testimonies in the field of history, diplomacy, culture, and other related areas. One example of such documents is the ducal letter from the Venetian Doge Francesco Donato, dated to the 16th century and kept in the State Archives in Pazin. The paleographic characteristics of the manuscript make the text partially legible because it was written on parchment that has a missing part. On the other hand, when it comes to diplomatic features, it can be concluded that it is an official epistle, written in a formal register according to the rules of ars dictaminis and ars notariae, characteristic of Renaissance Italian documents. It is precisely for that reason that this source represents a valuable testimony within the framework of cultural heritage, history, and diplomacy.
Keywords: Venice; Istria; doge; ducal letter; manuscript; epistle; epistolography; literary history; diplomatics; paleography